2004
DOI: 10.1029/2004je002249
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bands and ridges on Europa by cyclic deformation: Insights from analogue wax experiments

Abstract: [1] We perform a set of analogue wax experiments aimed at understanding the processes and conditions that lead to lineament formation on Europa. We heat a layer of wax from below and cool it from above so that a solid layer of wax forms above a molten layer, simulating either the liquid ocean or the actively convecting part of the ice shell. The solid layer of wax is then deformed periodically, simulating the cyclic strain caused by tides or by the satellite's nonsynchronous rotation. We find that the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…First, we have assumed that fold formation occurs under a constant horizontal velocity boundary condition, which yields a nearly-constant horizontal strain rate (the strain rate only decreases slightly as the lithosphere undergoes finite contraction). Although the assumption is consistent with models of band formation that assume a constant spreading rate (Prockter et al, 2002), Manga and Sinton (2004) suggested that Europa's bands and ridges can form by cyclic deformation of the ice shell driven by diurnal tides. In these models much of the extension is accommodated locally, and the degree to which any far-field lithospheric contraction and subsequent fold formation occurs is unclear.…”
Section: Discussionmentioning
confidence: 91%
“…First, we have assumed that fold formation occurs under a constant horizontal velocity boundary condition, which yields a nearly-constant horizontal strain rate (the strain rate only decreases slightly as the lithosphere undergoes finite contraction). Although the assumption is consistent with models of band formation that assume a constant spreading rate (Prockter et al, 2002), Manga and Sinton (2004) suggested that Europa's bands and ridges can form by cyclic deformation of the ice shell driven by diurnal tides. In these models much of the extension is accommodated locally, and the degree to which any far-field lithospheric contraction and subsequent fold formation occurs is unclear.…”
Section: Discussionmentioning
confidence: 91%
“…Our results also show that the morphologic width is larger than the measured expansion (Table ). Our results confirm previous studies that show that common bands are formed by expansion and strike‐parallel motion [ Head and Pappalardo , ; Prockter et al ., ; Manga and Sinton , ; Aydin , ].…”
Section: Resultsmentioning
confidence: 99%
“…A variety of models have been proposed to create lineaments on Europa, including diapirism [ Head and Pappalardo , ], processes analogous to spreading at Earth's mid‐ocean ridges to make bands [ Prockter et al ., ], folding of ductile ice to make both bands and ridges [ Manga and Sinton , ], shearing to make ridges by heating and thermal expansion of ice [ Nimmo and Gaidos , ], opening‐mode fractures [ Greenberg et al ., ], cryovolcanism [ Kadel et al ., ], rotating plates to form both bands and ridges [ Hoppa et al ., ], and shearing of opening‐mode fractures [ Aydin , ]. Each of these models predicts different lineament‐perpendicular displacements, permitting an observational test that can discriminate among many of these models.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments involving wax are therefore probably more relevant to the dynamics of ice satellites (e.g., Manga and Sinton, 2004) or of lava lakes. However, their relevance to mid-ocean ridge systems is still questionable for two reasons: first, dynamic similarity does not obtain, since the viscosity contrast between the solid and the liquid wax is much greater than the viscosity contrast across the solid lithosphere.…”
Section: Morphology Of Ridgesmentioning
confidence: 99%